2016
DOI: 10.7314/apjcp.2016.17.4.2093
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin-27 rs 153109 Single Nucleotide Polymorphism with Spontaneous Resolution of Hepatitis C Virus - Genotype 4a Infection in Egyptian Patients

Abstract: Background: HCV is a major global health problem. IL-27 is a member of the IL-6/IL-12 cytokine family with a broad range of anti-inflammatory properties. Recent studies highlighted the effect of a SNP in the IL-27 promoter region on modulating the progression of infectious diseases and individual responses to therapy. Aim of the work: The present study investigated the potential role of (-964 A/G) SNP in the promoter region of IL-27p28 gene (alleles rs153109) on the outcome of HCV infection among genotype 4a i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition, IL-27 was considered to be a potential biomarker for the diagnosis of PTB and TB pleurisy by comparing its expression level in pleural effusion and bronchoalveolar lavage fluid ( 21 , 22 ). Notably, the polymorphism in the IL-27 gene could regulate host innate and adaptive immune response and was associated with infectious diseases, autoimmune diseases, and caner ( 23 25 ). For example, the rs17855750 variant was considered to be a risk factor for papillary thyroid cancer in the Chinese population ( 23 ), and a protective factor for ulcerative colitis in the Mexican population ( 24 ), while rs153109 might contribute to virus clearance in hepatitis C virus (HCV) infection ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, IL-27 was considered to be a potential biomarker for the diagnosis of PTB and TB pleurisy by comparing its expression level in pleural effusion and bronchoalveolar lavage fluid ( 21 , 22 ). Notably, the polymorphism in the IL-27 gene could regulate host innate and adaptive immune response and was associated with infectious diseases, autoimmune diseases, and caner ( 23 25 ). For example, the rs17855750 variant was considered to be a risk factor for papillary thyroid cancer in the Chinese population ( 23 ), and a protective factor for ulcerative colitis in the Mexican population ( 24 ), while rs153109 might contribute to virus clearance in hepatitis C virus (HCV) infection ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the polymorphism in the IL-27 gene could regulate host innate and adaptive immune response and was associated with infectious diseases, autoimmune diseases, and caner ( 23 25 ). For example, the rs17855750 variant was considered to be a risk factor for papillary thyroid cancer in the Chinese population ( 23 ), and a protective factor for ulcerative colitis in the Mexican population ( 24 ), while rs153109 might contribute to virus clearance in hepatitis C virus (HCV) infection ( 25 ). However, our present study revealed no association between rs153109 and rs17855750 polymorphism in the IL-27 gene and susceptibility to PTB.…”
Section: Discussionmentioning
confidence: 99%